CH4 Emission Model from Bos Primigenius Waste in Fish-Water: Implications for Integrated Livestock-Fish Farming Systems - Okeniyi, Joshua O.; Ogunsanwo, Adedamola O.; Odiase, Nosadeba W.; Obiajulu, Uchechukwu E.; Okeniyi, Elizabeth T. (Journal of Engineering and Technological Sciences, 2013)
This paper studies a methane (CH4) emission model from the waste of cattle (B. primigenius) based on trends in integrated livestock-fish farming adoption by farmers in Nigeria. Dung of B. primigenius was employed as substrate in fish-water, obtained from a fish-rearing farm, as a matrix medium for simulating a low-oxygen wastewater environment of an agriculture-aquaculture system. A substrate to fish-water mass ratio of 1:3 was used, developed in a laboratory-size digesting reactor system. Volumetric readings, at ambient temperature conditions and with a retention time of thirty-two days, were then subjected to the logistic probability density function, and tested against correlation coefficient and Nash-Sutcliffe coefficient of efficiency criteria. The readings show that a volume of CH4-containing gas as high as 65.3Â x 10â3 dm3 was produced on the 13th day from the B. primigenius substrate. Also, production of 234.59Â x 10â3 dm3/kg CH4-containing gas, totaling 703.76Â x 10â3 dm3, was observed through the studied retention time. The 60% CH4 constituent model of the measured gas generation showed a potency of 2.0664 kg emission per animal, which is equivalent to 43.3944 CO2eq of global warming potential (GWP) annually per animal. This bears environmental and climate change implications, and therefore alternative sustainable practices for integrated livestock-fish farming adoption are suggested.